CONTRIBUTION OF BEEF CATTLE BUSINESS TO THE INCOME OF FARMERS FAMILY IN SIMALUNGUN REGENCY (CASE STUDY: IN SIMALUNGUN DISTRICT) - Linda Reni Suriani Purba; Wahyunita Sitinjak (SEAN Institute, 2023)
The purpose of this study was to determine the beef cattle business income and its contribution in running the beef cattle rearing business in farmer families in Simalungun Regency. The research method was carried out by survey and taking 30 samples by purposive sampling. The data analysis technique used is I = TR - TC where the cattle breeder business is included in the mix farming category and its contribution can reach 33% of the farmer's family income. In carrying out the research stages carried out such as identification of beef cattle maintenance, analyzing beef cattle business income and identification of business scale. The results of the research show that income from agriculture comes from income from working in agriculture, for example being an employee in a palm oil plantation, from paddy fields, yard and garden products, and those related to agriculture in a broad sense. In this study, most of the breeders were working on oil palm plantations and some came from plantations. The contribution to the total income of the farmer's family is 42%, and it is quite large because the farmer's income comes from beef cattle. This business is included in the category of Mixed Business Scale (Mix farming) income from livestock is 30% -70%, meaning that even though the income is not fully from raising beef cattle, the income of the livestock group is already dominant from beef cattle business activities. Beef Cattle Farming Business in Simalungun has prospects for development based on the contribution obtained by 33% of the total income of the whole farming family.